Effect of Motivation, Training and Compensation on Employee Performance at PT. Wahyu Septyan Bengkulu - Sandi Anugrah Hidayah; Siti Hanila; Rina Trisna Yanti (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the effect of motivation, training and compensation on employee performance at PT. Wahyu Septyan Bengkulu. The sample in this study were 60 employees of PT. Wahyu Septyan Bengkulu. The data were collected using a questionnaire and the method of analysis used was the rank spearman and the t test.The results of the Spearman rank analysis show that there is a significant influence of motivation (X1) on employee performance (Y) with the value of rho (ρ) = 0.631 in the criteria from 0.60 to 0.799 (strong), there is a significant effect of training (X2) on employee performance ( Y) with the value of rho (ρ) count = 0.687 in the criteria 0.60-0.799 (strong) and there is a significant effect of Compensation (X3) on employee performance (Y) with the value of rho (ρ) count = 0.678 in the criteria 0.60- 0.799 (strong). The results of the t test prove that there is a significant effect of motivation (X1) on employee performance (Y). It is known that the t value is 6,190 and this value shows that t is greater than t table (6,190> 1,671), there is a significant effect of training ( X2) on employee performance (Y), it is known that the t value is 7.192 and this value shows the t count is greater than the t table (7.192> 1.671) and there is a significant effect of compensation (X3) on employee performance (Y). t count is 7,017 and this value shows t count is bigger than t table (7,017> 1,671).